STRUCTURE AND VALIDATION OF A CONTEXTUAL QUALITY OF LIFE SCALE FOR PEOPLE WITH INTELLECTUAL DISABILITIES IN SOCIAL SERVICES: AN ORGANIZATION-ORIENTED MEASURE FROM AN EXTERNAL PERSPECTIVE - Moliner, Carolina; Gracia, Esther; Lorente, Laura; Martínez-Tur, Vicente (Perspectivas em Gestão & Conhecimento, 2013)
The aim of this study is to develop and validate a scale on the Quality of Life (QoL) of people with intellectual disabilities as assessed by family members (external perspective). The instrument measures improvement in QoL due to actions by organizations delivering services to individuals with intellectual disabilities (organization-oriented measure). In order to design the items for the scale, focus groups were set up with professionals dedicated to attending to individuals with intellectual disabilities. An initial scale of 20 items was constructed by consensus. A total of 1195 family members answered the questionnaire. In order to assess the structure of the scale, EFA recommended deleting 3 overlapping items. The final scale consisted of 17 items (α=95) and was composed of four main dimensions: self-determination (SD), social inclusion (SI), rights (RI) and overall improvement (OI), which explained 74.83% of the variance. Finally, the consistency and validity were assessed. Convergent validity and discriminant validity were satisfactory. Moreover, CFA confirmed the structure of the scale. Main conclusions, limitations and practical implications are discussed.